(untitled) (Fiep Bulletin - online, 2013)
This work has as objective to present the possible points of meeting between the Infantile Education and Basic Education being taken as reference two research of intervention with the daily pertaining to school of the Physical Education. For in such a way, I assumed the research-action as methodologyc referencial, whose instrument of collection of data was daily and half-structuralized interview. The data of the research evidence the necessity of studies with the daily one that they take the school as place of production and possibility of change.